159k views
1 vote
6x - 2y = 10

2x + 3y = 51
Solving the first equation above for y gives:
y =
X-5
DO NE

User Mohaps
by
5.3k points

2 Answers

0 votes

Answer:

y = 3x -5

Explanation:

6x - 2y = 10

-6x. -6x

Inverse Operations

-2y = -6x + 10

÷-2. ÷-2. ÷-2

y = 3x - 5

User Pepijn Kramer
by
5.7k points
3 votes

Answer:

6x – 2y = 10

2x + 3y = 51

Solving the first equation above for y gives:

y = (3) x – 5

Which choice shows the result of substituting

3x – 5 into the second equation for y?

2(3x – 5) + 3x = 51

----------2x + 3(3x – 5) = 51 its B

2(3x – 5) + 3y = 51

Solving the equation 2x + 3(3x – 5) = 51

for x gives x =

---6.

The complete solution to the system is:

----(6, 13)

Explanation:

User JCLL
by
5.5k points